PTU-189 Are the current management strategies for T1/T2 N0 oesophageal cancer optimal?. (28th May 2012) - Evans, J; Pande, R; Beardsmore, D; Corless, D; Crisp, W; Cheruvu, C
Abstract : Introduction: Currently patients with Stage 1 (T1/T2 N0) oesophageal cancer proceed straight to surgery; these patients have an expected 60%–90% 5 year survival. This staging is based on EUS (endoscopic ultrasound) and CT imaging, which are accurate in 90% and 70% for T stage respectively and 70% in N stage for EUS. However, reporting of postoperative histology reveals a significant proportion of these patients end up with locally advanced (T3 N1/0) disease, leading to a 5-year survival of 25%. The aim of this study is to assess the results based on the current UK protocols. Methods: This study includes all patients who underwent an oesophagectomy over a 4-year period (2008–2011), focusing on those with T1/T2 N0 disease. After comprehensive staging which included endoscopy, EUS, CT and PET scanning all patients results were reviewed. Data on patients with T1/T2 N0 disease who went straight to surgery were analysed. The primary end points included a review of the number of patients who had a higher staging on post-operative histology and also the peri-operative mortality, morbidity and survival. Results: 167 oesophagectomies were carried out during the study period in our institution, of which 26 (15.6%) were for preoperatively staged T1/T2 N0 disease (6 T1 and 20 T2). The mean age was 68 years and 18 (69.2%) of the patients were male. Ivor-Lewis oesophagectomies were performed on 23 patients, minimally invasive 3-stage procedures in 2 and 1 had a trans-hiatal operation. Post-operative histology indicated a higher stage of disease in 54% (14) of patients, 10 had a T3 lesion while 10 patients were noted to have nodal disease. One (3.8%) patient died on the 8th post-op day with bowel ischaemia and major or minor complications occurred in 11 (42%) of patients peri-operatively. Disease recurrence was seen in 4 (15.3%) patients at 15 to 18 months post-operatively, 3 (75%) of these had stage migration on histology to a higher stage and two have died. Conclusion: Our study concludes that in patients with T1/2 N0 oesophageal cancer, despite the high specificity and sensitivity of both EUS and CT scan we still seem to have a large proportion of patients who are under staged and often offered curative operations, which appear to result in sub-optimal management leading to early recurrence and poorer long-term outcomes. Further studies are essential for accurate assessment of this stage of disease so that appropriate treatment strategies can be implemented for the management of oesophageal cancer. Competing interests: None declared.